2009
DOI: 10.1002/ange.200901977
|View full text |Cite
|
Sign up to set email alerts
|

α‐Chiral Acetylenes Having an All‐Carbon Quaternary Center: Phase Transfer Catalyzed Enantioselective α Alkylation of α‐Alkyl‐α‐alkynyl Esters

Abstract: Owing to the synthetic versatility and modularity of acetylenes, chiral building blocks bearing acetylene moieties are widely used as valuable intermediates. [1] Accordingly, tremendous efforts have been devoted to the development of catalytic asymmetric approaches to enable facile access to these attractive materials. The asymmetric transition metal mediated addition of terminal acetylenes (asymmetric alkynylations) to various prochiral electrophiles (Scheme 1, left), [2] such as aldehydes, [3] ketones, [4] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The asymmetric isomerization of α‐methyl substituted alkynoate 2 a 6 was initially examined in the presence of 10 mol % of HB donor catalysts (Table 1). As expected, when benzothiadiazine catalyst 1 a 3c was used, the reaction of 2 a proceeded almost completely to afford the desired allenoate 3 a in good yield in a 92:8 ratio of 3 a and 2 a (entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…The asymmetric isomerization of α‐methyl substituted alkynoate 2 a 6 was initially examined in the presence of 10 mol % of HB donor catalysts (Table 1). As expected, when benzothiadiazine catalyst 1 a 3c was used, the reaction of 2 a proceeded almost completely to afford the desired allenoate 3 a in good yield in a 92:8 ratio of 3 a and 2 a (entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…The main thrust of this project was to develop a kinetic resolution technique to take advantage of the unprecedented nonmetal‐catalyzed cyclic heteroatom addition mentioned above. Nevertheless we briefly explored asymmetric phase‐transfer‐catalyzed additions of azidodicarboxylates to our γ‐silyl allenyl ester system by using a recent precedent by Maruoka and co‐workers involving carbon electrophiles 16. While aqueous/organic biphasic systems resulted in no reaction with allenyl oxyesters, we observed that CsOH⋅H 2 O in toluene led to their successful hydrazination.…”
Section: Methodsmentioning
confidence: 99%